Systematic reviews in dentistry: Current status, epidemiological and reporting characteristics - Bassani, Rafaela; Pereira, Gabriel Kalil Rocha; Page, Matthew J.; Tricco, Andrea C.; Moher, David; Sarkis-Onofre, Rafael (Journal of dentistry, 2019)
This study aimed to evaluate the epidemiological and reporting characteristics of systematic reviews (SRs) in dentistry indexed within PubMed during the year 2017. We searched for SRs in dentistry indexed within PubMed in 2017. Study selection was undertaken by two reviewers independently. Data related to epidemiological and reporting characteristics were extracted by one of three reviewers. A descriptive analysis of the data was performed. Characteristics of SRs were analyzed considering all SRs included and subgrouped by dental specialties. In addition, we explored if the reporting of 24 characteristics of treatment/therapeutic SRs was associated with the self-reported use of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement calculating the risk ratio (RR) with a 95% confidence interval for each characteristic. 495 articles fulfilled the eligibility criteria. The main specialty considered was Oral Surgery numbering 75 articles. Brazil presented the highest contribution with 117 SRs (23.6%). The reporting quality was variable. Items such as, use of the term “systematic review”, or “meta-analysis” in the title or abstract was well reported. In contrast, the study risk of bias/quality assessment method was not reported in 40.5% of SRs. In addition, only four reporting characteristics were described more often in those SR that reported using the PRISMA Statement. A large number of SRs were published in dentistry in 2017 and the reporting and epidemiological characteristics varied among dental specialties. There is a mandatory need to improve the quality of reporting and conduct of SRs in dentistry. Poor reporting and conduction of SRs could generate SRs with imprecise and biased results.